Structural and sedimentary discontinuities control the generation of karst dissolution cavities in a carbonate sequence, Potiguar Basin, Brazil. (January 2021) - Araújo, Renata E.B.; La Bruna, Vincenzo; Rustichelli, Andrea; Bezerra, Francisco H.R.; Xavier, Milton M.; Audra, Philippe; Barbosa, José A.; Antonino, Antônio C.D.
Abstract: Epigenetic karstic systems in carbonate rocks commonly result from progressive dissolution by acidic meteoric waters over thousands to millions of years. The generation of secondary porosity and permeability improvement due to dissolution in carbonate reservoirs of geofluids (e.g., groundwater, hydrocarbons, and CO2 ) can profoundly impact reservoir storage capacity and subsurface fluid flow. This study investigates the control of structural discontinuities such as stylolites, fractures, and primary sedimentary discontinuities on the generation of multiscale karst dissolution cavities by epigenetic fluid percolation in a Late Cretaceous carbonate sequence (Jandaíra Formation) in the Potiguar Basin, Northeastern Brazil. The study relies on micro- and macroscale analyses such as stratigraphic logs, field structural investigations, rock strength data collected in the field (Schmidt hammer), microtomographic and drone images, thin section analyses, porosity and permeability laboratory measurements. The results show that bed-perpendicular stratabound and non-stratabound stylolites and fractures can be enlarged due to meteoric water percolation until they merge and form a single channel system that crosscuts all sedimentary multilayers. Bed-parallel stylolites are ubiquitous in carbonate sequences overprinting bed interfaces and layers. Where not dissolved, bed-parallel stylolites have low porosity and permeability and thus can act as barriers to vertical fluid flow. Where dissolved, such stylolites can contribute to horizontal fluid flow and form channel porosity. The results of this study led to a formulation of a conceptual model of rock dissolution along structural and sedimentary discontinuities that affects carbonate rock successions in the subsurface. Highlights: We present the nature, distribution and development of stylolites, fractures, and sedimentary discontinuities. Structural and primary sedimentary discontinuities control the formation of dissolution cavities in carbonate rocks. This study characterizes dissolution processes along stylolites.